I OM - B - Zadanie 17

Dowieść, że jeżeli $ a \neq b $, to

\[<br />
a^3b + ab^3 < a^4 + b^4<br />
\]

Rozwiązanie

Ponieważ

\[<br />
\begin{split}<br />
(a^4 + b^4) - (a^3 b + ab^3) &= (a^4 - a^3b) + (b^4 - ab^3) \\<br />
&= (a - b)a^3 (a - b)b^3 \\<br />
&= (a - b)(a^3 - b^3) \\<br />
&= (a - b)(a - b) (a^2 + ab + b^2) \\<br />
&= (a - b)^2 (a^2 +ab + b^2) \\<br />
&= (a - b)^2 \left[(a + \frac{1}{2}b)^2 + \frac{3}{4}b^2\right],<br />
\end{split}<br />
\]

więc jeśli $ a \neq b $, to

\[<br />
(a^4 + b^4) - (a^3b + ab^3) > O,<br />
\]

skąd

\[<br />
a^3b+ab^3 < a^4+b^4.<br />
\]

Komentarze

Dodaj nową odpowiedź